2013
DOI: 10.1038/onc.2013.71
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus maintains lymphomas via its miRNAs

Abstract: Epstein-Barr virus (EBV) has evolved exquisite controls over its host cells, human B lymphocytes, not only directing these cells during latency to proliferate and thereby expand the pool of infected cells, but also to survive and thereby persist for the lifetime of the infected individual. Although these activities ensure the virus is successful, they also make the virus oncogenic, particularly when infected people are immunosuppressed. Here we show, strikingly, that one set of EBV’s miRNAs both sustain BL (Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(160 citation statements)
references
References 30 publications
5
152
2
1
Order By: Relevance
“…T cell-derived CD40 signaling may also help to induce IRF4 expression in LMP1-KO EBVinduced lymphomas (35). Finally, the viral encoded microRNAs (a portion of which are expressed by the B95.8 strain of EBV) were recently shown to promote the survival of BLs by inhibiting apoptosis (11), and likely contribute to the survival of LMP1-KO EBV-induced lymphomas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…T cell-derived CD40 signaling may also help to induce IRF4 expression in LMP1-KO EBVinduced lymphomas (35). Finally, the viral encoded microRNAs (a portion of which are expressed by the B95.8 strain of EBV) were recently shown to promote the survival of BLs by inhibiting apoptosis (11), and likely contribute to the survival of LMP1-KO EBV-induced lymphomas.…”
Section: Methodsmentioning
confidence: 99%
“…Although LMP1 is essential for the long-term outgrowth of EBV-transformed LCLs in vitro in the absence of a feeder layer (9), EBV-positive lymphomas in vivo often have more restricted forms of viral latency. For example, EBV-positive BLs, which are largely driven by MYC translocations, usually express only the EBNA1 protein (required for latent EBV genome maintenance), in addition to the virally encoded microRNAs and EBV-encoded small nuclear RNAs (EBER) (1,2,10,11). Furthermore, the majority of EBV-positive AIDS-related DLBCLs do not express detectable LMP1 protein (12).…”
Section: Introductionmentioning
confidence: 99%
“…Those that are encoded by EBV itself include BALF5 (21), LMP1 (22), LMP2A (23), and BHRF1 (23,24). Previously identified cellular targets include Bim (25), CAPRIN2 (24), CASP3 (26), DAZAP2 (27), DICER1 (28), E-cadherin (29), IPO7 (26,30), and PUMA (31). Many other candidate target genes have been identified by miRNA targetome studies (24,27,30,32); the biological significances of these miRNA-target interactions have yet to be clarified.…”
mentioning
confidence: 99%
“…Studies of EBV genomic deletions revealed that several miRNAs expressed from the BHRF1 locus (miRBHRF1s) play critical roles in B-cell transformation by inhibiting apoptosis and promoting cell cycle progression (Seto et al 2010;Feederle et al 2011). Consistently, expression of EBV miRNAs from the BamHI A rightward transcript (BART) locus is sufficient to prevent apoptosis in Burkitt's lymphoma (BL) cells or transformed primary B lymphocytes that have lost the EBV genome (Vereide et al 2014). Similarly, genetic deletion and complementation studies of KSHV miRNAs have shown that they promote cell cycle progression and inhibit apoptosis, necessary for cellular transformation (Moody et al 2013).…”
Section: Viral Mirnas: Small Rnas Big Rolesmentioning
confidence: 85%